Methodological Challenges in Studying Transformative Learning - Seon Joo Kim; Sharan B. Merriam (Adult Education Research Conference, 2011)
First discussed are philosophical perspectives in relation to the research design and methodology for studying transformative learning. Second, several promising research designs for studying this phenomenon are reviewed including narrative analysis, arts-based research, critical approaches, and action research. Finally, we conclude with a discussion of methodological challenges at this point in the evolution of the knowledge base of transformative learning.
Keywords: Transformative learning; methodological challenges